Peran Orang Tua Dalam Meningkatkan Hasil Belajar Siswa - Adi Kusmanto; Imam Muchlisin; Khoirul Anam (Al-Mada: Jurnal Agama, Sosial, dan Budaya, 2022)
The role of parents as first and foremost educators in the family is very important. The attention of parents greatly determines the pattern of behavior of their children, because in essence, parents play a major role in the education of their children, while teachers in schools are second educators after parents at home. This article aims to find out. What is the role of parents in improving the learning outcomes of class X students at SMA Al Muhammad Cepu? The research method used is descriptive qualitative. The data collection techniques are observation, interview, and documentation studies, while the data collection tools are observation sheets, interview guides, and field notes. The analysis in this study is presented in a qualitative descriptive manner. The results showed that: 1) the activities carried out by parents in guiding their children to learn were still not optimal; 2) the obstacles faced by parents in educating their children to study at home are that parents are busy so they do not have time, in addition to economic factors so that parents cannot provide learning facilities; 3) parents' efforts in overcoming obstacles in guiding children are parents trying to take the time to supervise children and provide guidance to children.